DEVELOPMENT OF MECHANICAL ENERGY TEACHING AIDS BASED ON ARDUINO UNO MICROCONTROLLER ASSISTED ULTRASONIC SENSORS AND LOAD CELLS - Matsun Matsun; Boisandi Boisandi; Ira Nofita Sari; Soka Hadiati; Deden Hidayat (Universitas Negeri Gorontalo, 2021)
The study aims to produce a mechanical energy prop by worthy using an Arduino Uno microcontroller assisted by an ultrasonic sensor and a load cell. The research method uses research and development design according to the ADDIE model which consists of 5 stages by analysis, design, development, implementation, and evaluation. The feasibility of mechanical energy props is determined according to experts. The research was carried out in 2021, a limited trial was carried out on students at SMA Negeri 3 Sungai Kakap. Research subjects' responses to the props are also known to use response questionnaires. The validation results of mechanical energy props based on the Arduino Uno microcontroller by two media experts obtained an average score of 95% in the excellent category and by two material expert validators, an average percentage of 97.21% was obtained in the excellent category. The response of research subjects to mechanical energy teaching aids based on the Arduino Uno microcontroller obtained an average score of 87.72% with an excellent category. Overall, mechanical energy teaching aids based on the Arduino Uno microcontroller assisted by an ultrasonic sensor and a load cell have been produced.